1969
DOI: 10.1111/j.1748-1716.1969.tb04415.x
|View full text |Cite
|
Sign up to set email alerts
|

An Electromyographic Analysis of Muscular Activity in the Hindlimb of the Cat during Unrestrained Locomotion

Abstract: During walking in unrestrained cats the electromyographic activity in many hindlimb muscles has been correlated with the angular movement in the hip, knee and ankle joints. The activity is rather uniform in the extensors but individual in different functional groups of flexor muscles. Observations on the precise timing of the onset of the main extensor activity suggest that it is not a reflex effect produced by stimulation of receptors (from muscle or skin) in the limb. It is assumed that the basic activity is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
150
6

Year Published

1977
1977
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 446 publications
(175 citation statements)
references
References 18 publications
17
150
6
Order By: Relevance
“…The difference may partly be explained by the different time courses of both types of locomotion. The second peak of activity in the knee flexors was only well developed during a rather fast trot and almost vanished during a slower walk (Engberg & Lundberg, 1969). Moreover, the walk described by these authors in the freely moving cat is much faster (about 0-6 s per step cycle) than the rhythm observed during fictive locomotion (about 3 s per step cycle).…”
Section: Discussionmentioning
confidence: 80%
“…The difference may partly be explained by the different time courses of both types of locomotion. The second peak of activity in the knee flexors was only well developed during a rather fast trot and almost vanished during a slower walk (Engberg & Lundberg, 1969). Moreover, the walk described by these authors in the freely moving cat is much faster (about 0-6 s per step cycle) than the rhythm observed during fictive locomotion (about 3 s per step cycle).…”
Section: Discussionmentioning
confidence: 80%
“…The subject-specific sequence of muscle onsets may result from a variety of factors, including electrode placement variation and/ or small fluctuations in motoneuron pool excitability. Further, although movement/muscle timing can be influenced by phasic (perturbation) stimuli (Gracco and Abbs, 1988a), it appears that the onset of muscle activity is primarily a central phenomenon (see also Engberg and Lundberg, 1969;Grillner and Zangger, 1975, for locomotion). The systematic relations in the time course of all muscle patterns (e.g., onsets and time to peak amplitude) and the resulting kinematic relations are consistent with a temporal scaling of central motor commands to all synergistic muscles (e.g., "common drive"; DeLuca et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…During locomotion, however, some motoneuron pools display activity during both the flexion and extension phases of the step cycle and there are differences in the onset and offset of activity in individual flexor and extensor pools (see Rossignol 1996). Originally it was suggested that proprioceptive afferent input was responsible for converting simple alternating flexor and extensor activity into a more complex pattern (Engberg and Lundberg 1969). The persistence of more complex activity patterns following bilateral deafferentation of the hindlimbs in decerebrate cats, however, led Grillner and Zangger (1975) to conclude that the locomotor CPG "… does not simply generate an alternate activation of flexors and extensors but a more delicate pattern that will sequentially start and terminate the activity in the appropriate muscles at the correct instance".…”
mentioning
confidence: 99%